"I" see Samsung, but "we" see Samsung and LG: The moderating role of consumers' self-construals and perceived similarity in spillover effect of product-harm crisis. (January 2020) - Wu, Xiao Xiao; Choi, Woo Jin; Park, JaeHong
Negative spillovers due to firms' product-harm crises have attracted the attention of marketing researchers owing to the devastating and irrecoverable damage they can cause. Despite the extensive research undertaken on this topic, studies concerning spillovers across competing brands from different companies are relatively scant. Drawing upon self-construal theory, we propose that spillover effects across competing brands from different companies may vary depending on consumers' self-construal and on the perceived similarity between the brands. The results of two studies show that, when the brands' perceived similarity is high, the spillover effect of a product-harm crisis on a competing brand from a different company is greater for consumers with interdependent self-construal than for those with independent self-construal. Our findings extend the theoretical knowledge of spillover effects and provide meaningful managerial implications for global corporations.